Realitas Kompetensi Komunikasi antar Budaya pada Proses Adaptasi Pelajar Indonesia di Luar Negeri - Luthfia, Amia (Bina Nusantara University, 2012)
There are more and more Indonesian students studying abroad. Having competence in communicating with people from different cultures is very important in order to avoid conflicts between cultures, and so that the communication occurs effectively and properly. This study examines intercultural communication competence Indonesian people when they are being assigned to study in Australia, with qualitative methodology. The method used is field observations and in-depth interviews. The context of the research is very limited, that examines only one group of students assigned to study for less than one year at the institution which have prepared a special program for them. The results of this study are the students quite competent in intercultural communication, especially in formal social contexts. However, in informal social contexts, they are not competent enough. They can be quite competent in the formal social context as they are aided by educational setting that more accommodative and tolerant of their shortcomings compared to the informal social context.